Stress Granule Formation is One of the Early Antiviral Mechanisms for Host Cells Against Coxsackievirus B Infection - Zhai, Xia (Virol Sin, 2018)
Stress granules (SGs) are intracellular granules formed when cellular translation is blocked and have been reported to be involved in a variety of viral infections. Our previous studies revealed that SGs are involved in the coxsackievirus B (CVB) infection process, but the role of SGs in CVB infection has not been fully explored. In this study, we found that CVB type 3 (CVB3) could induce SG formation in the early phase of infection. Results showed that levels of CVB3 RNA and protein were significantly inhibited during the early stage of CVB3 infection by the elevated formation of SGs, while viral RNA and protein synthesis were significantly promoted when SG formation was blocked. Our findings suggest that SG formation is one of the early antiviral mechanisms for host cells against CVB infection.